2016
DOI: 10.15447/sfews.2016v14iss1art7
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Water Supply Effects of Ending Groundwater Overdraft in California's Central Valley

Abstract: Surface water and groundwater management are often tightly linked, even when linkage is not intended or expected. This link is especially common in semi-arid regions, such as California. This paper summarizes a modeling study on the effects of ending long-term overdraft in California's Central Valley, the state's largest aquifer system. The study focuses on economic and operational aspects, such as surface water pumping and diversions, groundwater recharge, water scarcity, and the associated operating and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The Central Valley of California is an example where groundwater consumption has been estimated to be annually around 60% of the total water storage changes (snow water equivalent, surface water, soil moisture, and groundwater) in the basin (Famiglietti et al, 2011). Intensive groundwater withdrawals in the valley have contributed to depletion of streams (Fleckenstein et al, 2004), subsidence and irreversibly reducing storage (Farr & Liu, 2015;Faunt et al, 2016), drying up of wells and increased cost of pumping (Nelson et al, 2016), and disconnection of stream-aquifer systems (Bolger et al, 2011;Dogrul et al, 2016), among others. All these studies emphasize that the groundwater resources are under high pressure, their sustainability is at risk, and therefore, they need to be replenished as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The Central Valley of California is an example where groundwater consumption has been estimated to be annually around 60% of the total water storage changes (snow water equivalent, surface water, soil moisture, and groundwater) in the basin (Famiglietti et al, 2011). Intensive groundwater withdrawals in the valley have contributed to depletion of streams (Fleckenstein et al, 2004), subsidence and irreversibly reducing storage (Farr & Liu, 2015;Faunt et al, 2016), drying up of wells and increased cost of pumping (Nelson et al, 2016), and disconnection of stream-aquifer systems (Bolger et al, 2011;Dogrul et al, 2016), among others. All these studies emphasize that the groundwater resources are under high pressure, their sustainability is at risk, and therefore, they need to be replenished as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although California's overdraft occurs mostly in its Central Valley (DWR ), eliminating groundwater overdraft is expected to have statewide effects (Nelson et al. ). Scanlon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al. () and Escriva‐Bou et al. () have concluded that ending groundwater overdraft requires reducing net water use or increasing surface water imports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations